PILKADA LANGSUNG: KISAH SUKSES DAN PROBLEMATIKA - Jamaludin, Teten (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2019)
The implementation of direct local election has become important part of Indonesian society. This election is achievement of the reform. The public can finally vote for their head of the region (the local leaders) based on their own aspiration. The mechanism of this local election is somehow facing pro and contra between direct and indirect. It is considering the positive and negative impacts of the mechanism. The positive impact is to provide an opportunity for proposing their own people of the region to be candidate. This opportunity as a constitutional right of citizen regardless of race, ethnicity, and religion. Other results that there are number of regions are developed since this direct election able to produce several local leaders who are innovative and creative in developing their regions. In contrary, not few of the regional head are entangled with corruption cases. This is caused by the high cost of politics to achieve the seat of that regional head andco-head of the region. In addition, the cost to run the local election is also extremely expensive. Besides the local election socially triggers the horizontal conflict especially among the regional elites and its supporters. Different from the indirect local election that the cost is less. However,its has shortcoming that the regional head electedare not directly reflecting the aspirations of its people.